1971
DOI: 10.2134/agronj1971.00021962006300050037x
|View full text |Cite
|
Sign up to set email alerts
|

Internal Water Status and Water Transport in Seed Onion Plants1

Abstract: Water potential, transpiration rate, and stomatal resistance of the various parts of the onion (Allium cepa L.) plant were measured under field and controlled conditions. Water potentials of florets and pedicels were always lower than leaf water potentials. Water potential difference between the florets and the soil of as much as —9 bars were found. The greatest drop in water potential was found between the flowers and the upper part of the seed stalk. These differences in water potential were found even when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
1
1

Year Published

1972
1972
2000
2000

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 9 publications
4
32
1
1
Order By: Relevance
“…4). Such an abrupt increase in r1 at a particular qi has been observed previously (1,3,(9)(10)(11)14), with the critical if varying with species from -6 bars in onion (14) to -14 bars in vine (11) and sunflower (1). Moreover, in snap beans the critical if varied with the leaf surface, the stomata on the adaxial epidermis closing at a higher i f than those on the abaxial epidermis (1).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…4). Such an abrupt increase in r1 at a particular qi has been observed previously (1,3,(9)(10)(11)14), with the critical if varying with species from -6 bars in onion (14) to -14 bars in vine (11) and sunflower (1). Moreover, in snap beans the critical if varied with the leaf surface, the stomata on the adaxial epidermis closing at a higher i f than those on the abaxial epidermis (1).…”
Section: Discussionsupporting
confidence: 77%
“…In previous studies with maize and sorghum, stomatal closure occurred at a lower l in sorghum than in maize (17), but the V/ at which stomatal closure was observed was higher (less negative) than in the present study (3, 17). However, both the former studies were conducted in a growth room, and other studies have indicated that field-grown plants have a lower critical if than those grown in a growth room (1, 4, 9, 10, 14) possibly because of a lower 7r in field-grown material (14).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, growth was correlated with stomatal conductance and not turgor potential. A direct rela- STOMATAL CONDUCTANC tion between growth rate and stomatal conductance has been reported by others (1,5).…”
Section: Discussionsupporting
confidence: 58%
“…Inúmeras variáveis fisiológicas, tais como o nível de ácido abscísico, a fotossíntese líqui-da, a transpiração, a condutância estomática, entre outros, são correlacionáveis com o potencial total de água na planta ou seus componentes; daí, o interesse na avaliação dessa variável em estudos de relações hídricas de plantas (Hsiao, 1973). Segundo Millar et al (1971), muitos pesquisadores têm dado preferência às determinações do potencial total da água na planta, porque ele influencia mais diretamente os processos metabólicos que qualquer outro parâmetro de avaliação do déficit hídrico. Entretanto, Acevedo et al (1979) relatam que as medições do potencial hídrico, isoladamente, não fornecem informações suficientes sobre o impacto do estresse hídrico nos processos fisiológicos medidos pelo conteúdo de água dos tecidos.…”
Section: Introductionunclassified